2021
DOI: 10.1109/jsen.2020.3040995
|View full text |Cite
|
Sign up to set email alerts
|

Flexible, Highly Sensitive Paper-Based Screen Printed MWCNT/PDMS Composite Breath Sensor for Human Respiration Monitoring

Abstract: Accurate measurement and monitoring of respiration is vital in patients affected by severe acute respiratory syndrome coronavirus -2 (SARS-CoV-2). Patients with severe chronic diseases and pneumonia need continuous respiration monitoring and oxygenation support. Existing respiratory sensing techniques require direct contact with the human body along with expensive and heavy Holter monitors for continuous real-time monitoring. In this work, we propose a low-cost, non-invasive and reliable paper-based wearable s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 58 publications
0
20
1
Order By: Relevance
“…The same is true in reality; subjects 3 and 4 swam or exercised about 5 times a week, while subject 2 only exercised almost once a week. In any case, all five subjects in our experiment were fitter than the subject in reference [ 35 ], since the BI calculated of subject in our experiment is much smaller than that of subject in reference [ 35 ], which reached 3.37. Results showed that both the resonant frequency and reflection coefficient S 11 can be used to efficiently predict the fitness of individual, especially for athletes.…”
Section: Resultscontrasting
confidence: 51%
“…The same is true in reality; subjects 3 and 4 swam or exercised about 5 times a week, while subject 2 only exercised almost once a week. In any case, all five subjects in our experiment were fitter than the subject in reference [ 35 ], since the BI calculated of subject in our experiment is much smaller than that of subject in reference [ 35 ], which reached 3.37. Results showed that both the resonant frequency and reflection coefficient S 11 can be used to efficiently predict the fitness of individual, especially for athletes.…”
Section: Resultscontrasting
confidence: 51%
“…In another study, an interdigitated electrode strain gauge was reported by a gauge factor of around 8.24, which was fabricated by conventional screen printing of multiwalled carbon nanotubes and PDMS composite on a paper substrate. Although the gauge factor of the capacitive strain gauge has been improved, the stretchability is not enough for human motion detection, and it would be applicable for small strain detection such as human respiration detection [52].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps, face mask wearing enforcement in densely populated places is one of the most effective means to stop the spread of virus, as respiratory face masks are highly effective in blocking most respiratory droplets and aerosols. , Despite these efforts, the increase in reported cases of COVID-19 continues, which has led to an urgent need for more effective ways to combat the coronavirus and restore society to a certain semblance of normalcy. To address this, smart face masks made by equipping respiratory face masks with electronic sensors and modules have been recently proposed. To date, smart masks are mainly used for two purposes: (1) to monitor respiratory symptoms, such as cough, , and (2) to enhance the filtration of airborne pathogens including coronaviruses; ,, both contribute to prevention and control of respiratory diseases. In addition to the significance in diminishing the pandemic, there has been a witnessed trend of smart masks and wearables for their potential in health monitoring and preventive care, personalized behavior modeling, and healthcare internet-of-things (IoTs). Nevertheless, existing research largely ignores wearing comfort and breathability, which are crucial for user experience and compliance of wearing face masks.…”
mentioning
confidence: 99%
“…The proposed smart face mask consists of a zero-power radio frequency (RF) harmonic transponder, which is attached to the inner side of an ordinary face mask and can be torn off and reattached for repeated usage (Figure b). To achieve better wearing comfort than current smart masks, ,, the RF harmonic transponder is printed using spray-printed silver nanowires (AgNWs) on the multiscale porous polystyrene- block -poly­(ethylene- ran -butylene)- block -polystyrene (SEBS) substrate (Figure c); both nanomaterials are lightweight, flexible, stretchable, and, most importantly, breathable. Moreover, the 0.2–7 μm pores of the SEBS substrate can efficiently block the sunlight, while allowing transmission of the human-body infrared (IR) radiation (which is in some sense similar to a spectral filter), thereby enabling passive heat dissipation and/or passive cooling .…”
mentioning
confidence: 99%
See 1 more Smart Citation